The 5-M Downsizing Communication Model for Survivor-Employee Engagement - Ehondor, Beryl A. (Journal of Organizational Psychology, 2024)
The global economic crisis has led to downsizing, creating survivor-employees and affecting employee-engagement. This study aimed to assess the relationship between banks’ internal communication strategies and their survivor-employee engagement. The research involved in-depth interviews and descriptive design, focusing on 15 commercial banks in Nigeria. The findings revealed that downsizing is prevalent in the industry, with no protection from Nigerian labour laws. The downsizing-communication from top management to survivor-employees is minimal, leading to survivor syndrome and declining employee-engagement. The study created and proposed the 5M-model for downsizing communication and employee engagement. The 5M-model framework connotes Mobilisation, Management, Motivate, Monitor and Measure. However, the 5M-model for downsizing-communication and employee-engagement amplifies the media richness theory, integrates employee-engagement theory and caters for downsizing communication phenomena, a new solution-dimension for optimal employee-organisation relationship. The 5M model communication gradient transits from green to yellow indicating efficacy of communication, the capacity to convey meaning between sender and receiver, record reactions and get immediate feedback. This novel model is a template to improve survivor-employee engagement and employee-organization relationships.